Effect of different type of polymer concentration on asymmetri polysulfone membrane for CO2/CH4 separation - Nur Amira, Abdullah (2010)
The objective of this study is to developed polysulfone (PSU) asymmetric membrane for gas separation and to identify the concentration of polysulfone in dope solution to produce high selectivity membrane for CO2/CH4 gas separation. Polysulfone was selected as the polymer material in this research since it is glassy type polymer that exhibit good mechanical properties compare to others while 1-Methyl-2-Pyrrolidone (NMP) is chosen as the solvent because it is low toxicity and completely miscible with water, organic acid and alcohol. Polysulfone asymmetric membrane was prepared by mixing a dope, where polysulfone polymer was mixed with 1-Methyl-2Pyrrolidone (NMP). Three sample of solution was prepared with different type of concentration of polysulfone polymer which is 20 wt%, 25 wt% and 30 wt% respectively. Before perform gas permeation test, polysulfone membrane was coating with PDMS and n-hexane with the composition 3 wt% and 97 wt% respectively. Permeation test was carried out by using single gas permeation test by testing gas carbon dioxide (CO2) and methane (CH4). The membranes were characterized by using Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Through SEM analysis, the morphology and structure of the membrane at 20 wt% concentration of polysulfone shows structural pores using 1000 magnification. Membranes with 30 wt% of PSU exhibits the most selective membrane with selectivity about 2.619 while membrane with 20 wt% shows the lowest selectivity that is 1.22. This is because the increasing polysulfone polymer concentration resulted a denser and thicker skin layer of membrane so that the membrane with high polysulfone concentration become more selective but less permeability to the gas separation.